The Influence of Loose Parts Media on Children's Fine Motor Skills - Ummi Zahidah; Amir Hamzah; Indah Dwi Sartika; Muhamad Fauzi (EDUCATIO : Journal of Education, 2024)
This research was motivated by issues related to the fine motor skills of children at RA Darussalam Menanti, specifically: 1) Some children exhibited stiffness and slowness in properly coordinating their eyes and hands during fine motor activities; 2) Some children experienced difficulty in creating shapes using the media materials provided at the school; 3) Some children struggled with accurately pasting images onto their worksheets. The objective of this study was to determine whether the use of Loose Parts Media has an impact on the fine motor skills of Group B children at RA Darussalam Menanti. The research employed a Pre-Experimental Design method, specifically using a One Group Pre-test Post-test design. The sample consisted of 15 children, including 10 boys and 5 girls. Data collection techniques included observation, tests, and documentation. The data analysis techniques utilized in this study were Normality Test, Homogeneity Test, and Hypothesis Testing. Hypothesis results were obtained after conducting both the pre-test and post-test. The researchers then analyzed the study's findings. Data analysis results were examined through hypothesis testing using a t-test, which yielded a t-value (t